Implementasi Program Takhassus Al-Qur’an di Pesantren Ashabiq Kota Sukabumi - Ressy Resviati Putri; Siti Qomariyah; Lia Aliyah; Leni Sumarni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to determine the implementation of the Takhassus Al-Qur'an Program in tahfidz-based schools, with a focus on curriculum, teaching methods, evaluation, as well as supporting and inhibiting factors that influence its success. This program is designed to form a generation of Al-Qur'an memorizers who excel in academic and spiritual aspects. The background to this research is the importance of developing a comprehensive Al-Qur'an education program to support the achievement of quality memorization, as well as the challenges faced in its implementation. This research uses a qualitative approach with case study and phenomenology methods, which involves in-depth interviews with program managers, teachers and students, as well as observations of program implementation. The research results show that the curriculum implemented is systematic and includes realistic memorization targets, tahsin, tajwid, and moral development. Teaching methods such as tikrar, simai, and wahdah are effective in supporting the memorization process, although challenges such as fatigue, boredom, and time constraints often hinder students. Supporting factors, including family support and intensive teacher guidance, strengthen the success of this program. In conclusion, synergy is needed between teachers, students and the school to optimize the implementation of the Takhassus Al-Qur'an Program.